Optimalisasi Penggunaan SDKI, SLKI, dan SIKI dalam Penyusunan Dokumentasi Keperawatan di Ruang IGD RS Tipe B Kota Malang - Wahyuningsih, Indri; Herlianita, Risa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Nursing documentation carried out by nurses in carrying out the nursing process includes components of assessment, data analysis, nursing diagnosis, intervention, nursing implementation and evaluation. The nursing process is an inseparable part of nursing care services. A nursing process that is carried out well is one of the indicators for determining the assessment of the quality of nursing care services in a hospital. One component to be able to realize quality nursing care is the nursing documentation aspect. Good documentation is beneficial for patients, nurses and hospitals and can be used as a guide to provide quality services. Nursing documentation carried out by partners in using the SDKI, SLKI and SIKI guidelines has not been carried out optimally and well integrated. The output resulting from this service activity is an increase in nurses' understanding of the use of SDKI, SLKI and SIKI so that it can be applied more optimally, as well as the preparation of emergency nursing documentation forms based on SDKI, SLKI and SIKI.